Ditiocarbamatos derivados do glicoluril, ácido úrico, ácido parabânico e hidantoína: compostos de coordenação e uso como inibidores de corrosão do bronze - Joao Cura D Ars de Figueiredo Junior (2008)
This thesis work is about dithiocarbamates compounds, their synthesis, study and application as corrosion inhibitors. The dithiocarbamates herein studied were synthesized from four substances: glycoluril, uric acid, parabanic acid and hydantoin. The pro-ligands were synthesized through reaction with CS2 and NaOH, characterized via elemental analysis (CHN) and vibrational spectroscopy in the infrared, conductivity and they have the following stoichiometries: DTC glycoluril - Na4C8H2N4O2S8, DTC uric - NaC6H3N4O3S2 . H2O, DTC parabanic - Na2C5N2O3S4, DTC hydantoine - NaC4H3N2O2S2 . 3H2O. Coordination compounds were synthesized through traditional synthesis with these pro-ligands and Cu(NO3)2.3H2O, CuSO4.5H2O e Pb(NO3)2 but no reasonable stoichiometries were determined using results from elemental analysis and absorption spectroscopy. This problem was attributed to formation of various oligomers. Templated metal synthesis was utilized. Through this strategy was possible to determine the stoichiometry of six compounds: Cu DTC glycoluril - [Cu4(C7H3N4O2S6) (CH3CH2OH)2] (NO3)2, Cu DTC uric [Cu6(C9N4O3S8)2 (CH3CH2OH)7] (NO3)4, Cu DTC parabanic - [Cu3(C5N2O3S4)2 (H2O)4] (NO3)2, Cu DTC hydantoine - [Cu3(C5H2N2O2S4)2 (H2O)7] (NO3)2, Pb DTC glycoluril - [Pb4(C8H2N4O2S8)(CH3CH2OH)14(Pb(SH)3)2] and Pb DTC uric - [Pb8(C9N4O3S8)4(CH3CH2OH)16(H2O)4]. The compounds synthesized through both strategies were characterized via vibrational and electronic spectroscopy. The compounds synthesized through templated metal synthesis were further characterized via electrospray mass spectroscopy (ESI/MS), thermogravimetry (TG), differential thermogravimetry (DTG), differential thermoanalysis (DTA) and proton nuclear magnetic ressonance (1H NMR). After characterization of coordination compounds, it was started the study of these compounds as corrosion inhibitors of bronze TM 23. Quantum chemistry calculations were performed at B3LYP functional density level of theory. These calculations were done in order to obtain HOMO and LUMO energy values, important data to study inhibition efficiency. Weight loss tests and electrochemical essays (polarization curves and cyclic voltametry) were performed to measure inhibition efficiencies of these pro-ligands as films and in acid HNO3 solution, NaCl solution and salt spray cabinet. Characterization of bronze surface and corrosion products were performed via scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Corrosion rates and inhibition efficiencies were calculated via these essays and the pro-ligands acted as mixed type inhibitors. The process of film formation were studied via adsorption isotherms, infrared reflection absorption spectroscopy (IRRAS) and cyclic voltametry. The results showed that pro-ligands adsorbs on surface through chemisorption, except DTC parabanic in saline media and DTC hydantoine in both media. The films are made of coordination compounds. The reaction of pro-ligands with paratacamite, CuCl2. 3Cu(OH)2, an usual bronze corrosion product, in acidic media, generates coordination compounds. The pro-ligand DTC uric was hydrolyzed in this acidic media and was considered inappropriate as bronze corrosion inhibitor in this media.